2000
DOI: 10.1017/s0006323199005423
|View full text |Cite
|
Sign up to set email alerts
|

Why do females mate multiply? A review of the genetic benefits

Abstract: The aim of this review is to consider the potential benefits that females may gain from mating more than once in a single reproductive cycle. The relationship between non-genetic and genetic benefits is briefly explored. We suggest that multiple mating for purely non-genetic benefits is unlikely as it invariably leads to the possibility of genetic benefits as well. We begin by briefly reviewing the main models for genetic benefits to mate choice, and the supporting evidence that choice can increase offspring p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
1,405
8
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,595 publications
(1,440 citation statements)
references
References 354 publications
23
1,405
8
4
Order By: Relevance
“…Recent studies suggested that genetic benefits drive not only pre-copulatory but also post-copulatory female choice in animals. 11,33,34 Genetic compatibility is more easily detected post-copulation via signals on sperm, and sperm-soma or egg-sperm interactions. 34 No other study has sought evidence for MHCmediated prenatal selection in newborns despite that this is an expected consequence of various observations regarding the influence of the MHC on reproductive physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that genetic benefits drive not only pre-copulatory but also post-copulatory female choice in animals. 11,33,34 Genetic compatibility is more easily detected post-copulation via signals on sperm, and sperm-soma or egg-sperm interactions. 34 No other study has sought evidence for MHCmediated prenatal selection in newborns despite that this is an expected consequence of various observations regarding the influence of the MHC on reproductive physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative sources of variation are related to species‐specific reproductive, demographic or behavioral traits. For instance, clutch size can contribute to multiple paternity rates, particularly in the context of bet‐hedging (Jennions and Petrie 2000), but there was no significant difference in brood size between the two Cyprichromis species. A more likely source of mating pattern variation are potential between‐species differences in the densities of males and females within the school, which can influence mating patterns (Reichard et al.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple paternity can also reflect females seeking benefits from mating with more than one male (Arnqvist and Nilsson 2000; Jennions and Petrie 2000; Taylor et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, it raised the questions as to why females would pursue and benefit from matings outside the social pair bond (Westneat et al 1990;Petrie and Kempenaers 1998), and why a female would benefit from mating with more than one male for a given clutch or litter. This new focus on females brought attention to the issue of polyandry more generally (Jennions and Petrie 2000;Simmons 2005;Parker and Birkhead 2013;Pizzari and Wedell 2013).…”
mentioning
confidence: 99%